Gatifloxacin Pharmacokinetics/Pharmacodynamics-based Optimal Dosing for Pulmonary and Meningeal Multidrug-resistant Tuberculosis - Deshpande, D; Pasipanodya, JG; Srivastava, S; Bendet, P; Koeuth, T; Bhavnani, SM; Ambrose, PG; Smythe, W; McIlleron, H; Thwaites, GE; Gumusboga, M; Van Deun, A; et al. (Oxford University Press, 2018)
Background: Gatifloxacin is used for the treatment of multidrug-resistant tuberculosis (MDR-TB). The optimal dose is unknown.